PESANTREN WOMEN COMMUNITY'S RESPONSE TO THE INDONESIAN ULEMA COUNCIL (MUI) FATWA ON PALESTINE: A PORTRAIT OF URBAN MUSLIM RELIGIOUS LIFE IN METRO CITY - Anwar, Mustofa; Fatiha, Belgheddouche; Ridwan, Mohammad; Saputra, Edy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
This study examines the religious responses of pesantren-based Muslim women in urban Indonesia to the fatwa issued by the Indonesian Ulema Council (MUI) supporting Palestine. The research focuses on the Jam'iyyah Perempuan Pengasuh Pesantren dan Muballighah (JP3M) in Metro City, employing a qualitative phenomenological approach through in-depth interviews, observation, and documentation. The findings reveal three main dimensions in interpreting the fatwa: Islamic solidarity (ukhuwah Islamiyah), humanitarian solidarity (ukhuwah insaniyah), and contextual understanding. These dimensions manifest in community actions such as fundraising, digital campaigns, and public education, integrating religious values with modern practices. The study indicates that religious literacy, access to global information, and local social dynamics shape the religious expressions of urban Muslim women. However, the geographically limited context of Metro City may influence the findings due to regional cultural factors, community social structures, and institutional access, which may not reflect other urban settings. Therefore, comparative studies involving similar communities across diverse regions must capture a broader spectrum of religious responses. Moreover, a multidisciplinary approach combining perspectives from sociology, religious studies, and digital technology is essential to provide a more comprehensive and contextually relevant analysis of this complex global religious phenomenon.